Characteristics of sleep patterns in adolescents: comparisons between Saudi Arabia and the UK - Wasmiah Bin Eid (2023)
There are concerns regarding sleep deprivation among adolescents, especially with mounting evidence for the importance of sleep during puberty, and its effects on health and families. The present study aimed to characterise sleep in typical development (TD) adolescents in Saudi Arabia, and compare their sleep profiles to TD adolescents in the UK, to evaluate sleep patterns in adolescents in Saudi Arabia, and to examine the relationship between sleep patterns and the use of social media in both groups. Findings from the current study reported a shorter sleep duration for the Saudi Arabia group than in previous studies and the UK group, which may be attributed to the lack of sleep hygiene practised in Saudi Arabia. Multiple analysis of variance results found significant differences in daytime sleepiness (p < 0.001) and a preference for morningness/eveningness (p < 0.001) between Saudia Arabia and UK adolescents. Statistically significant negative correlations (p > 0.05) between the duration of social media usage and sleep duration were found in both the Saudi Arabia and UK adolescents, where a lower number of sleep hours was observed with a higher duration of social media use. This study fills a gap in the research of sleep in Saudi Arabia in adolescents, and offers important insights on the comparison in sleep habits between Saudi Arabia and UK adolescents.